Anatomic Derkay Score Is Associated with Voice Handicap in Laryngeal Papillomatosis in Adults. (23rd February 2016) - Kupfer, Robbi A.; Çadalli Tatar, Emel; Barry, Jonnae O.; Allen, Clint T.; Merati, Albert L.
Abstract : Objective: The Derkay staging system quantifies recurrent respiratory papillomatosis (RRP) severity based on involvement of laryngeal structures. Despite its broad use in the laryngology literature, the association between Derkay score and voice‐related quality of life has not previously been studied. It is hypothesized that Derkay score positively correlates with the Voice Handicap Index–10 (VHI‐10). Study Design: Case series with chart review. Setting: Tertiary medical center. Subjects and Methods: Forty‐six adult RRP patients treated from 2007 to 2013 at a tertiary medical center were included. Anatomic Derkay scores at the time of each RRP procedure were calculated. VHI‐10 scores obtained within 30 days preceding the procedures were used to assess for correlation between Derkay staging system and VHI‐10. Results: Ninety‐three procedures performed on 46 patients met inclusion criteria. Mean Derkay score was 11.9 (range, 2‐28), and mean VHI‐10 was 18.0 (range, 0‐40). There was a significant positive correlation between Derkay score and VHI‐10 (Spearman coefficient r = 0.42, P <. 0001). Conclusion: The anatomic burden of RRP as assessed by Derkay staging system is positively correlated with voice‐related quality of life as quantified by the VHI‐10.